Brick Structures: Durable Bones for Affordable Housing Rehab (International Journal of Environmental Sciences, 2024)
This study discusses how rehabilitating brick structures can be a cost-effective and sustainable way of curbing the global affordable housing crisis. The economic, environmental, and social advantages of repurposing older brick edifices are seen in the research to help underline the huge amount of money saved in a comparison of the costs of rehabilitation suites at an average of around $120-$150 per square foot versus $200-$300 in new construction development. This research highlights the challenge of modern upgrades, which include efficient windows, increased insulation, and modern HVAC systems that can minimize energy use by 20-25$ and cut down the costs of long-term maintenance by 15-20%. Reusing the brick material also saves a solid 4,500 kg of CO2 per ton, which greatly lowers the carbon emissions. The study also outlines major hindrances, such as financial and bureaucratic constraints, and proposes implementing policy changes and fostering social-business collaboration to help achieve these rehabilitation targets. Rehabilitating the brick buildings as affordable housing creates a stable working community and promotes economic growth and development by maintaining the historical and cultural value of neighborhoods. Future studies must align with long-term sustainability and technological advancement to enhance the sustainability of such projects globally.